Outdoor recess is associated with more positive attitudes toward physical activity among pre-adolescent students and their parents - Lemberg, Getter Marie; Kull, Merike; Mäestu, Jarek; Riso, Eva-Maria; Mägi, Katrin; Mäestu, Evelin (Frontiers in Sports and Active Living, 2024)
Schools are ideal settings for implementing various physical activity (PA) interventions considering the amount of time students spend in school. School culture and various activities included in the school schedule can be important factors in developing positive attitudes toward PA and the behavioral habits of students. In the current study, we investigated students' and their parents' perceptions of outdoor recess and PA opportunities in schools with different recess opportunities. In addition, it was explored whether the recess opportunities are related to students' leisure-time PA. Our main finding was that students in schools with outdoor recess on every day and their parents had significantly more positive attitudes about outdoor recess and PA opportunities in school. Furthermore, students in schools with outdoor recess on every day stated being significantly more active during their leisure time compared to students in other groups. These results emphasize the positive effect schools can have on students' PA levels by implementing outdoor recess in the school schedule. The results of the current study also encourage stakeholders to make a daily outdoor recess a reality, fostering positive attitudes about PA and increased PA levels of students.